2012
DOI: 10.1186/1755-1536-5-s1-s5
|View full text |Cite
|
Sign up to set email alerts
|

The myofibroblast, multiple origins for major roles in normal and pathological tissue repair

Abstract: Myofibroblasts differentiate, invade and repair injured tissues by secreting and organizing the extracellular matrix and by developing contractile forces. When tissues are damaged, tissue homeostasis must be re-established, and repair mechanisms have to rapidly provide harmonious mechanical tissue organization, a process essentially supported by (myo)fibroblasts. Under physiological conditions, the secretory and contractile activities of myofibroblasts are terminated when the repair is complete (scar formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
144
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(152 citation statements)
references
References 37 publications
0
144
0
8
Order By: Relevance
“…This αSMA-induced mechanical stress plays a considerable role in the contraction and maturation of the granulation tissue-new connective tissue that forms on the wound surface during the injury healing process. 27 As the number of myofibroblasts is much higher in the tumor microenvironment, αSMA has become one of the go-to markers for identifying CAF populations. 28,29 In addition to its role as a marker for cancer-associated fibroblasts, αSMA has also been identified as a prominent prognostic factor in tumor patients.…”
Section: Fapmentioning
confidence: 99%
“…This αSMA-induced mechanical stress plays a considerable role in the contraction and maturation of the granulation tissue-new connective tissue that forms on the wound surface during the injury healing process. 27 As the number of myofibroblasts is much higher in the tumor microenvironment, αSMA has become one of the go-to markers for identifying CAF populations. 28,29 In addition to its role as a marker for cancer-associated fibroblasts, αSMA has also been identified as a prominent prognostic factor in tumor patients.…”
Section: Fapmentioning
confidence: 99%
“…B, Proposed evolution of PFs, MSCs, and RQFs in development and aging, and matching cellular plasticity (fibroblast activation protein), FSP1/S100A4 (fibroblast-specific protein 1), THY1/CD90 (Thy1.1 and Thy1.2 in mice), and αSMA (alpha-smooth muscle actin, encoded by ACTA2); these are seen in CAFs as well.4,5 αSMA is typically associated with a distinct subtype of fibroblast referred to as myofibroblasts (Table 1).4,6,40 The reorganization of the actin skeleton in myofibroblasts together with αSMA expression may enhance their contractile properties in wound healing. 40 Since αSMA+ myofibroblasts are usually absent in normal interstitial spaces (with the exception of smooth muscles cells in perivascular niches), but increase in number in fibrotic or cancerous lesions, they are often thought of as pathology-associated fibroblasts.…”
Section: Lipofibroblastsmentioning
confidence: 99%
“…In rodents (mice and rats), genetic tools for lineage tracing are available. With this advantage, it has recently been shown that there are multiple fibroblast subpopulations with distinct functions and that myofibroblasts have multiple origins in wound healing (reviewed by Driskell & Watt, 2015;Micallef et al, 2012). The formation of fibrous scar tissue, fibrosis, which is mediated by myofibroblasts, is not restricted to injured skin but is widely observed in other tissues after chronic damage.…”
Section: Wound Healing Of Skin By Fibrosis In Mammals-origin Of Fibmentioning
confidence: 99%